2017
DOI: 10.1021/acs.chemmater.7b03750
|View full text |Cite
|
Sign up to set email alerts
|

First-Principles Analysis of Li Intercalation in VO2(B)

Abstract: Bronze-phase vanadium dioxide VO 2 (B) is notable as a promising cathode material for high-capacity Li ion batteries. While various forms of VO 2 (B) nanostructures have been experimentally investigated, a comprehensive theoretical understanding of the lithium storage mechanism is still lacking. In this research, we examine the redox mechanism, structural evolution, electronic characteristics, and the kinetics of Li ion diffusion in VO 2 (B) by first-principles calculations. The impact of the surface environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 79 publications
4
31
0
Order By: Relevance
“…The structural evolution of VO 2 has been experimentally and computationally studied for Li, Na, Mg, and Al‐ion batteries . It is especially noteworthy that the intercalation of multivalent Mg and Al‐ions into VO 2 is typically accompanied by strong deformation of the crystal structure .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The structural evolution of VO 2 has been experimentally and computationally studied for Li, Na, Mg, and Al‐ion batteries . It is especially noteworthy that the intercalation of multivalent Mg and Al‐ions into VO 2 is typically accompanied by strong deformation of the crystal structure .…”
Section: Resultsmentioning
confidence: 99%
“…When the A sites are occupied, the protons are positioned at the center of four O atoms that bridge the V 4 O 10 bilayers (Figure C). At H 0.25 VO 2 , the vertical distance between the two V 4 O 10 bilayers increases, and as a consequence, the protons occupying the A sites no longer align themselves in the middle of the b axis tunnel . As the H concentration x increases from 0.25 to 0.5, the protons start to insert onto the B sites.…”
Section: Mechanistic Insightsmentioning
confidence: 98%
“…The mechanical properties of these fibers are normally probed by nano indentation method. Li et al [26] and Cao et al [27] have conducted extensive studies on mechanical properties of E-glass fibers and carbon fibers by using nano indentation method. According to them the change in elastic modulus of E-glass fibers does not affect the hardness and elastic modulus.…”
Section: Measurementsmentioning
confidence: 99%
“…According to them the change in elastic modulus of E-glass fibers does not affect the hardness and elastic modulus. They also reported that as the E-glass fibers and PAN-CFs in fiber form cannot be measured using conventional mechanical testing technique, the nano indentation is a very powerful method for studying the mechanical properties of these short fibers [26,27]. The manufacturers specifications of mechanical and physical properties of E-glass fibers and AS4C grade PAN-CF are given in Table 1.…”
Section: Measurementsmentioning
confidence: 99%
“…where F denotes the Faraday constant. Stable intermediate phases formed throughout discharge are the ones on the convex hull of the formation energy vs. Na content plot [19,30]. Formation energies (E f ) adjusted to the energies of pristine and fully sodiated VO 2 were…”
Section: Methodsmentioning
confidence: 99%